Performance of evacuated flat plate solar thermal collectors. (December 2018) - Moss, Roger; Shire, Stan; Henshall, Paul; Arya, Farid; Eames, Philip; Hyde, Trevor
Highlights: Two evacuated collectors built and tested. Flooded panel absorber performed as expected. Significant reduction in heat loss when evacuated. Toughened glass with pillar supports proved robust. Solder edge seal degraded due to thermal expansion stresses. 66% higher annual output at 85 °C than from evacuated tubes. Abstract: Heat losses from a flat panel solar collector can be significantly reduced by lowering the internal pressure to <0.5 Pa. Compared with conventional collectors, the resulting increase in efficiency is predicted to give a significant gain in annual heat output in the context of a temperate climate with low median irradiance. Two experimental collectors were built and tested to investigate theoretical aspects of evacuated flat plates and develop appropriate technological solutions. One had a metal tray to the rear, the other used two sheets of glass. An array of pillars supports the glass against atmospheric pressure. The experimental procedure was designed to minimise measurement uncertainty. Testing under a solar simulator, with and without a vacuum, showed a sudden drop in heat loss as the pressure was reduced below 0.5 Pa. When evacuated the heat loss coefficient fell from 7.43 to 3.65 W/m 2 K and the efficiency at a nominal test condition of ΔT = 60 °C, G = 1000 W/m 2 increased from 36% to 56%. Heat losses from absorber to glass were within 9% of the predicted level. This demonstrates that the heat loss mechanism is well understood.